Pengaruh Model Pembelajaran Gallery Walk terhadap Communications Skill Siswa pada Pembelajaran IPS - Silvana, Regita Dwi (IJOCE: Indonesia Journal of Civic Education, 2026)
This study aims to determine the effect of the Gallery Walk learning model on the Communication Skills of eighth-grade students in social studies at SMP Negeri 22 Bengkulu. The background of this study is based on the importance of Communication Skills as one of the 21st-century skills that students must possess to support active and collaborative learning processes. The research method used was a quantitative method with a quasi-experimental design (Non-equivalent Control Group Design). The study population was all eighth-grade students at a public junior high school in Bengkulu City, with two classes taken by purposive sampling: an experimental class and a control class. Data collection instruments used were observation sheets, questionnaires, and communication tests. The results showed a significant difference between the Communication Skills of students taught using the Gallery Walk model and those taught using conventional methods. This is evidenced by the t-test results, which obtained a significance value (Sig.) <0.05. Thus, it can be concluded that the Gallery Walk learning model has a positive effect on improving students' Communication Skills in social studies.   Keywords: Gallery Walk, Communication Skills, Social Studies Learning, Grade VIII Students